Knockout of Noxa with CRISPR/Cas9 Increases Host Resistance to Influenza Virus Infection - Ao Zhou; Wenhua Zhang; Baoxin Wang; Xia Dong; Jing Zhang; Hongbo Chen (Cellular Microbiology)
The influenza virus induces cellular apoptosis during viral propagation, and controlling this virus-induced apoptosis process has been shown to have significant antiviral effects. The proapoptotic BH3-only protein Noxa is a strong inducer of apoptosis that can be activated by this virus, suggesting that Noxa has the potential as an anti-influenza target. To assess the value of Noxa as an antiviral target, we utilized CRISPR/Cas9 technology to produce a Noxa-knockout cell line. We found that the knockout of Noxa resulted in a dramatic reduction in the cytopathic effect induced by the influenza virus. Moreover, Noxa knockout decreased the expression of influenza viral proteins (NP, M2, HA, and NS2). In addition, Noxa deficiency triggered a complete autophagic flux to weaken influenza virus-induced autophagosome accumulation, indicating that Noxa may be a promising antiviral target for controlling influenza virus infections.